Comparison of Short-Course Radiotherapy Versus Long-Course Radiotherapy for Treatment of Metastatic Spinal Cord Compression: A Systematic Review and Meta-Analysis. Issue 43 (October 2015) - Qu, Song; Meng, Hui-Ling; Liang, Zhong-Guo; Zhu, Xiao-Dong; Li, Ling; Chen, Ling-Xiao; Zhou, Zhi-Rui
Abstract : Abstract: In this study, we evaluate the efficacy of short-course radiotherapy (SCRT) versus long-course radiotherapy (LCRT) in the treatment of metastatic spinal cord compression (MSCC). PubMed, EMBASE, and Web of Science were searched up to April 2015. Relevant data were extracted based on inclusion and exclusion criteria. Methodological quality of randomized controlled trial (RCT) was evaluated using modified Jadad scale; non-RCT was evaluated using Newcastle-Ottawa Scale. Meta-analysis was performed using RevMan 5.3 software. Fourteen studies with 2239 patients were included. Results of meta-analysis showed that there were no significant differences between SCRT and long-course radiotherapy LCRT in 6-month overall survival rate (risk ratio [RR] = 0.97, 95% confidence interval [CI] 0.88, 1.07, P = 0.55), 1-year overall survival rate (RR = 0.94, 95% CI 0.85, 1.04, P = 0.22), motor function improvement (RR = 0.96, 95% CI 0.81, 1.13, P = 0.63), no change on motor function (RR = 0.98, 95% CI (0.88, 1.09), P = 0.74], and deterioration on motor function (RR = 0.96, 95% CI 0.71, 1.31, P = 0.78). Compared with SCRT, LCRT significantly increased 6-month local control rate (RR = 0.87, 95% CI 0.80, 0.95, P = 0.002), 1-year local control rate (RR = 0.83, 95% CI 0.71, 0.97, P = 0.02), and 2-year local control rate (RR = 0.83, 95% CI 0.79, 0.87, P < 0.00001). Both LCRT and SCRT provided similar survival rates and functional outcome, but LCRT showed better local control rates than SCRT. However, considering low cost and good patient's compliance, SCRT may be a better choice.